The use of social accountability mechanisms by Syrian diaspora organizations providing aid in the Syrian crisis - Mounah Abdel-Samad; Shawn Flanigan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper presents data from a study of Syrian diaspora organizations providing assistance to conflict-affected Syrians in Europe, the Middle East, and North America. Using interview data from leaders in three Syrian diaspora non-profit organizations, this paper examines the social mechanisms used to ensure accountability within the challenging environments where the organizations operate. We find that Syrian diaspora organizations benefit from informal social accountability mechanisms that derive from individuals' social network ties. Personal, social forms of accountability are particularly valuable to these organizations because these mechanisms help circumvent uncertainty and challenges in the operational environment. These findings reflect an important theme in the extant literature on diaspora philanthropy: diaspora members may have an advantage over other actors because of dense personal networks that make them adept at identifying dependable partners and enforcing agreements even in places where banking and legal systems are fragile. The leaders in our study rely on trusted individuals as a mechanism to ensure financial accountability and to assess the trustworthiness of potential partners on the ground in Lebanon, Syria, and Turkey.
Keywords: 330; Syria; diaspora philanthropy; accountability; forced migration; non-governmental organizations